2016
DOI: 10.1177/1088868316640974
|View full text |Cite
|
Sign up to set email alerts
|

The Social Psychology of Intergroup Toleration

Abstract: The global increase in cultural and religious diversity has led to calls for toleration of group differences to achieve intergroup harmony. Although much social-psychological research has examined the nature of stereotyping, prejudice, and discrimination, and its impact on targets of these biases, little research has examined the nature and impact of toleration for intergroup relations. Toleration does not require that people give up their objections to out-group norms and practices but rather mutual accommoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(129 citation statements)
references
References 191 publications
(205 reference statements)
2
120
0
7
Order By: Relevance
“…Therefore, some critics argue that tolerance functions as a subtle social mechanism contributing to domination and inequality (Insel, ; Marcuse, ), and to the depoliticization of diversity by reducing structural disadvantages to cultural group frictions (Brown, ). The theoretical implication is that tolerance should not only be studied in terms of meaningful differences in moral values and beliefs, as we have done here, but also in terms of intergroup processes, as we have discussed more fully elsewhere (Verkuyten & Yogeeswaran, ). For example, the notion of tolerance is not only useful to argue for the acceptance of minority group practices and beliefs, but also for construing an ingroup‐favoring moral distinction between “us” and “them”.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, some critics argue that tolerance functions as a subtle social mechanism contributing to domination and inequality (Insel, ; Marcuse, ), and to the depoliticization of diversity by reducing structural disadvantages to cultural group frictions (Brown, ). The theoretical implication is that tolerance should not only be studied in terms of meaningful differences in moral values and beliefs, as we have done here, but also in terms of intergroup processes, as we have discussed more fully elsewhere (Verkuyten & Yogeeswaran, ). For example, the notion of tolerance is not only useful to argue for the acceptance of minority group practices and beliefs, but also for construing an ingroup‐favoring moral distinction between “us” and “them”.…”
Section: Discussionmentioning
confidence: 82%
“…Mutual tolerance is therefore vital for the functioning of open, plural societies encompassing many different social, ethnic, cultural, or religious groups (Popper, ; Rawls, ; Scanlon, ). However, as noted by Verkuyten and Yogeeswaran (), tolerance has received astonishingly little systematic attention in social psychological research, despite its importance as a pressing social issue.…”
Section: Introductionmentioning
confidence: 86%
“…First, disapproval serves as a definitional condition, because it makes little sense to say we tolerate someone or something that we already approve of. This insight has previously been formulated by political scientists (Gibson, Duch, & Tedin, , p. 338; Sullivan, Piereson, & Marcus, ) as well as political philosophers (Forst, ; Scanlon, ), but is now also increasingly shared by social psychologists (Klein & Zick, ; Verkuyten & Yogeeswaran, ). Second, the model specifies respect for others as the critical process component that operates as a counterweight to the disapproval of others’ beliefs, preferences, or practices (Forst, ).…”
Section: Introductionmentioning
confidence: 99%
“…Developmental theories of social identity [Abrams & Rutland, 2008;Nesdale, 2008;Nesdale et al, 2005;Verkuyten & Yogeeswaran, 2017] have demonstrated age-related changes regarding group identity, group norms, and group dynamics. This work has provided a basis for examining intergroup attitudes in morally relevant contexts using the SRD model.…”
Section: Srd Modelmentioning
confidence: 99%
“…In particular, considerations regarding the treatment of others with respect to their group membership explicitly or implicitly factor into moral decisions across the life span. Humans are members of many social groups, including families and friendship networks as well as broad affiliations like gender and ethnicity [Verkuyten & Yogeeswaran, 2017]. This means that it is necessary to understand not only how individuals reason about concepts such as equality, but also what they think about others in terms of their group identity and psychological states.…”
mentioning
confidence: 99%